KERAGAAN AGROINDUSTRI BACANG AYAM EL SHADDAI FOOD MELALUI PEMASARAN KONVENSIONAL DAN ONLINE DI KECAMATAN PENJARINGAN, KOTA JAKARTA UTARA - Evelyn Faviana; Dyah Aring Hepiana Lestari (Lampung University, 2021)
This study aims to analyze the raw materials procurement based on six right components, standard cost, distribution channels, marketing margins, and the role of supporting services. This research uses a case study method at El Shaddai Food Agroindustry, Penjaringan District, North Jakarta City. The research data were collected in December 2019 to February 2020 and the data analyses method used were qualitative and quantitative descriptive analyses. The results showed that the six components of raw material procurement process had been done precisely. The standard cost of chicken bacang was less than the selling price so the business was profitable and the marketing channels consisted of two channels. Support services that have been utilized to the fullest were market and transportation.Key words: agroindustry, bacang, marketing, online, performance